Some Recent Advances in the Understanding of Gas-Solid Interactions during the Gasification of Brown Coal and Biomass - Li, Chun-Zhu (John Wiley & Sons, Inc., 2010)
Gasification is the core of many advanced energy technologies that achieve high efficiences and low emissions of greenhouse gases and other pollutants, particularly with the utilisation of brown coal and biomass. There are strong gas-solid interactions inside a gasifier. Our recent studies have shown that the gas-solid interactions should be an important consideration in the design and operation of a gasifier for brown coal or biomass. The gas-solid interactions could greatly change the char gasification rates by influencing the structure of char as well as the forms of the inherent catalytic species during gasification. In particular, the interactions between volatiles and char influence many aspects of the reactions involving char, and could almost terminate the gasification of char in the worst case. The essence of volatile-char interactions is believed to be the reactions involving radicals, especially H radicals. An overview of the progress in the author's research group in this area will be provided.